Hypovitaminosis D and bone mineral metabolism and bone density in hyperthyroidism. - Dhanwal, D; Kochupillai, N; Gupta, N; Cooper, C; Dennison, E (2010)
Little is known about the impact of concomitant vitamin D deficiency on bone mineral density in hyperthyroidism. Therefore, we evaluated bone mineral measures in vitamin D-deficient and sufficient patients with hyperthyroidism. Thirty newly diagnosed consecutive patients with hyperthyroidism were included. Blood samples were used for measurement of calcium, phosphate, alkaline phosphatase, 25-hydroxy vitamin D [25(OH) D], and parathyroid hormone (PTH). Bone mineral density (BMD) was measured at the hip, spine, and forearm. The patients were divided into vitamin D-deficient (< 25 nmol/L) and vitamin D-sufficient groups (≥ 25 nmol/L). Eight (26.6%) patients had 25(OH) D levels less than 25 nmol/L, with mean ± standard deviation (SD) level of 16.5 ± 3.2 (vitamin D-deficient group 1), and the remainder had a mean ± SD of 46.0 ± 13.5 nmol/L (vitamin D-sufficient group 2). Serum-intact PTH levels were significantly higher in group 1 compared with those in group 2 (31.2 ± 16.3 vs 18.0 ± 13.1 pg/mL; p=0.041). In the vitamin D-deficient group, the mean BMD T-scores were in the osteoporotic range at hip and forearm (-2.65 ± 1.13 and -3.04 ± 1.3) and in the osteopenia range at lumbar spine (-1.83 ± 1.71). However, in vitamin D-sufficient group, the mean BMD T-scores were in the osteopenia range (-1.64 ± 1.0, -1.27 ± 1.6, and -1.60 ± 0.7) at hip, forearm, and lumbar spine, respectively. The mean BMD Z-scores were also significantly lower in vitamin D-deficient group compared with those in vitamin D-sufficient group. Finally, BMD values (gm/cm(2)) at the hip and forearm were significantly lower in the vitamin D-deficient group compared with those in the vitamin D-sufficient group. In conclusion, hyperthyroid patients with concomitant vitamin D deficiency had lower BMD compared with vitamin D-sufficient patients.